″Facilitative approach in the process of developing research competence of future Doctors of Philosophy in the system of postgraduate education″ - Oliinyk, I. V. (Problems of Engineer-Pedagogical Education, 2018)
The present paper explains the role of the facilitative approach in the process of developing research competence of future Doctors of Philosophy within the system of postgraduate education and analyzes definitions of the terms "facilitation" and "facilitative method" currently existing in pedagogical and psychological studies. The article describes the most effective methods of facilitation, which ensure the development of cognitive activity, practical research skills, scientific and research abilities, creativity. Among such methods the author of the present work highlights the following ones: ―Open Space‖ Technology, ―International Café‖ and ―Grape Cocktail‖ Technologies, Dynamic Facilitation, Graphic Facilitation, Appreciative Inquiry, Scamper Technology, ―Six Hats‖ Method, ―635‖ Method, Classic Brainstorming, Mind Mapping, Delfi Method, Walt Disney Strategy, Cluster Assembly Method, Web-Quest (Educational Web-Quest), ―Five ‗Whys?‘‖ Method, Fishbone Method (Fish Skeleton).